1999
DOI: 10.4141/s98-013
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and N source influence soil-emitted nitrous oxide in the Alberta Parkland region

Abstract: Lemke, R. L., Izaurralde, R. C., Nyborg, M. and Solberg, E. D. 1999. Tillage and N source influence soil-emitted nitrous oxide in the Alberta Parkland region. Can. J. Soil Sci. 79: 15-24. Zero tillage systems are receiving attention as possible strategies for sequestering atmospheric carbon. This benefit may be offset by increased N 2 O emissions, which have been reported for soils under zero tillage (ZT) compared to those under more intensive tillage (IT). Comparisons of N 2 O emissions from the two systems h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 14 publications
8
95
3
Order By: Relevance
“…The higher CH 4 -uptake and increased C sequestration, however, do not counterbalance the greater N 2 O-fluxes under NT; this results in an overall negative greenhouse gas balance of 214 kg CO 2 -equivalents·ha -1 ·yr -1 . However, it is evident from the error terms [126] for the (sub)tropical soils and from [13,16,17,25,48,117,158,159,171,174,178,179,199,215] for the temperate soils.…”
Section: Greenhouse Gas Balance For No-tillagementioning
confidence: 99%
“…The higher CH 4 -uptake and increased C sequestration, however, do not counterbalance the greater N 2 O-fluxes under NT; this results in an overall negative greenhouse gas balance of 214 kg CO 2 -equivalents·ha -1 ·yr -1 . However, it is evident from the error terms [126] for the (sub)tropical soils and from [13,16,17,25,48,117,158,159,171,174,178,179,199,215] for the temperate soils.…”
Section: Greenhouse Gas Balance For No-tillagementioning
confidence: 99%
“…Incorporation of crop residues provides a source of readily available C and N, which is believed to induce a higher CH 4 release from rice paddies [Denier van der Gon and Neue, 1995;Wang, 1999] and to influence N 2 O emissions [Aulakh et al, 1991;Cochran et al, 1997;Flessa and Beese, 1995;Lemke et al, 1999]. Decomposition of incorporated organic material is the predominant source of methanogenic substrates in early stage of rice growing [Watanabe and Roger, 1985], and CH 4 emission via ebullition during this period contributes significantly to the total emissions of this gas .…”
Section: Introductionmentioning
confidence: 99%
“…For mineral fertilizers Lemke et al (1999) showed enhanced N 2 O emissions for approximately 4 d following fertilization at Ellerslie in 1994; Corre et al (1996) did not observe significant fertilizer-induced emission for several weeks after N inputs until a major rainfall occurred. Obviously, the soil water status at the time of N inputs will largely determine this lag although Müller et al (2002Müller et al ( , 2004) also note that the lag time will differ for specific N 2 O producing processes.…”
Section: Temporal Sample Spacing For Short-duration Emission Eventsmentioning
confidence: 90%
“…Clearly there will always be an interaction between the costs of sampling multiple sites and the resources available. However studies such as those of Corre et al (1996) and Lemke et al (1998Lemke et al ( , 1999 demonstrate that multi-year sampling of a range of sites is possible at an intensity required to yield reliable data.…”
Section: Spatial Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation